2018
DOI: 10.1038/s41393-018-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity and preservation of skeletal muscle mass in people with spinal cord injury

Abstract: Study design Cross-sectional Objective To investigate the association between skeletal muscle mass and spasticity in people with spinal cord injury (SCI). Setting Tertiary level hospital in Seoul, Korea Methods Spasticity was evaluated in 69 participants with SCI using the spasticity sum score (SSS), Penn Spasm Frequency Scale (PSFS), and Spinal Cord Assessment Tool for Spastic Reflexes (SCATS). Skeletal muscle mass was measured using a dual-energy X-ray absorptiometry scanner, and skeletal muscle index was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Muscle shortening is also thought to be a factor that contributes to muscle atrophy (Baker and Matsumoto 1988;Pierotti et al 1991), hence the presence of contractures could also explain differences in the amount of muscle atrophy. In contrast, it has been suggested that muscle spasticity may actually reduce the effects of disuse atrophy by maintaining muscle contractions (Cha et al 2019). There are therefore several factors contributing to the amount of muscle atrophy besides the amount of torque the muscle is able to produce.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle shortening is also thought to be a factor that contributes to muscle atrophy (Baker and Matsumoto 1988;Pierotti et al 1991), hence the presence of contractures could also explain differences in the amount of muscle atrophy. In contrast, it has been suggested that muscle spasticity may actually reduce the effects of disuse atrophy by maintaining muscle contractions (Cha et al 2019). There are therefore several factors contributing to the amount of muscle atrophy besides the amount of torque the muscle is able to produce.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural electrical stimulation (ESS) is a promising technique for improving motor recovery in chronic patients with SCI (69,70). Preliminary results showed that the application of ESS improving both motor control and muscle mass in the lower extremity of patients with severe paralysis or plegia (Figure 1).…”
Section: Epidural Electrical Stimulationmentioning
confidence: 99%
“…This mechanism is different from that obtained by FES since muscle contraction is mainly indirect. Interestingly, spasticity, which is another indirect, reflex activity in patients with SCI, is associated with partially preserved muscle mass (70).…”
Section: Epidural Electrical Stimulationmentioning
confidence: 99%
“…Researchers have shown that spasticity can preserve the muscle mass through muscle contraction in patients with SCI. [ 6 , 7 ] A few studies have proposed that spasticity may affect glucose metabolism positively, as it maintains fat-free mass (FFM) and prevents muscle atrophy in patients with only motor complete SCI. [ 8 - 10 ] In the present study, we aimed to investigate the impact of spasticity on glucose metabolism and FFM in both patients with motor complete SCI and patients with motor incomplete SCI.…”
Section: Introductionmentioning
confidence: 99%